Queen, Mother, and Stateswoman : Mariana of Austria and the Government of Spain - Mitchell, Silvia Z. (Book collections on Project MUSE., 2019)
"A reassessment of the regency of Queen Mariana of Austria (1634-1696) during the minority of her son, King Carlos II of Spain, offering a new perspective on the Spanish monarchy in the later seventeenth century"--Provided by publisher